Is an ethical status confessionis possible? - Rauhaus, Alfred (HTS teologiese studies, 2009)
This article argues that it is possible to declare a status confessionis on account of ethical issues. Discussions of the last 50 years confirm this. The article clarifies under what circumstances a status confessionis may be declared. It is always necessary to indicate clearly that the confession of the church is affected by the ethical situation in question. It is not suffi cient to give a general reference to the gospel or to the teaching of Christ as the reason for declaring a status confessionis.